An extracellular matrix extract for tissue-engineered cartilage. - Lum, L.Y (IEEE Engineering in medicine and biology magazine)
Cartrigel modulates the chondrogenic effect of TGF-β3 on mesenchymal stem cells in photopolymerizing hydrogels. Tissue engineering of cartilage in photopolymerizing PEG-based scaffolds may benefit from the incorporation of ECM extracts for greater control of cell behavior.